2013
DOI: 10.1371/journal.pone.0053906
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-221 Induces Cell Survival and Cisplatin Resistance through PI3K/Akt Pathway in Human Osteosarcoma

Abstract: BackgroundMicroRNAs are short regulatory RNAs that negatively modulate protein expression at a post-transcriptional and/or translational level and are deeply involved in the pathogenesis of several types of cancers. Specifically, microRNA-221 (miR-221) is overexpressed in many human cancers, wherein accumulating evidence indicates that it functions as an oncogene. However, the function of miR-221 in human osteosarcoma has not been totally elucidated. In the present study, the effects of miR-221 on osteosarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(163 citation statements)
references
References 61 publications
(92 reference statements)
8
153
0
Order By: Relevance
“…A B OS cells. These findings are also concordant with those of previous studies, which indicated that the PI3K/Akt pathway has a critical role in cancer chemoresistance (22)(23)(24)(25). Of note, the selective PI3K inhibitor only blocked ~50% of the effect of PCX on cisplatin chemoresistance and cell survival in OS cells, suggesting the involvement of other signaling pathways, which may be identified in further studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A B OS cells. These findings are also concordant with those of previous studies, which indicated that the PI3K/Akt pathway has a critical role in cancer chemoresistance (22)(23)(24)(25). Of note, the selective PI3K inhibitor only blocked ~50% of the effect of PCX on cisplatin chemoresistance and cell survival in OS cells, suggesting the involvement of other signaling pathways, which may be identified in further studies.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated that the PI3K/Akt pathway is important for cancer cell chemoresistance (22)(23)(24)(25). Therefore, the present study examined the effects of PCX on the activity of PI3K and phosphorylation of Akt in OS cells.…”
Section: Effects Of Pcx On Pi3k Activity and Phosphorylation Of Akt Imentioning
confidence: 95%
“…miR, microRNA. phosphoinositide 3-kinase/Akt pathway (27). Furthermore, increased levels of miR-128 are negatively correlated with PTEN levels, and increased proliferation of MG63 and U2OS OS cells (28).…”
Section: Discussionmentioning
confidence: 97%
“…They negatively regulate gene expression through base-pairing to the 3'-untranslated region (UTR) of target messenger RNA (mRNA), resulting in the inhibition of translation and mRNA degradation (4,5). Beyond involvement in diverse biological processes, including cell growth, apoptosis, development, differentiation and endocrine homeostasis (6), emerging evidence indicates that the deregulation or dysfunction of miRNAs contribute to human carcinogenesis and cancer progression (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%